Alchemy & mysticism: the hermetic museum - Roob, Alexander (Bibliotheca universalis, 2019)
Macrocosm -- The world Ptolemy, Brahe, Copernicus -- Sun -- Moon -- Cosmic time -- Lower astronomy -- Stars -- Music of the spheres -- Genesis -- Eye -- Cosmic egg -- Opus magnum -- Genesis in the retort Elementa chemicae -- Purification -- Fall of Adam -- Chaos -- Saturnine night -- Torment of the metals -- Resurrection -- Aurora Light & Darkness Jacob Bohme's system -- Ladder -- Ramon Lull's system -- Philosophical tree -- Sephiroth -- Ab uno -- Fortress -- Animal riddles -- Oedipus chimicus -- Dew Mute book -- Women's work & child's play -- Vegetable chemistry -- Serpent -- Return Theosophical Society -- Conjunctio Rosarium philosophorum -- Androgyny -- Separatio -- Hermetic Yantras -- Trinity -- Fire Philosophical egg -- Matrix -- Fountain -- Christ-Lapis -- Blood -- Microcosm -- Human Form Divine -- Brain & memory -- Signatures -- Script & seal -- Apparitions -- Rotation -- Whirl & magnet -- Divine Geometry -- Wheel Winds, Gurdjieff's eneagramm, Colour wheel -- Rose -- Pilgrim.